CARL and MPL in Cuban patients with essential thrombocythemia and primary mielofibrosis - Fernández Martínez, Lesbia; Garrote Santana, Heidys; Amor Vigil, Ana María; Díaz Alonso, Carmen Alina; Fernández Águila, Julio Dámaso; Lavaut Sánchez, Kalia; Lam Díaz, Rosa María; Quintero Sierra, Yamilé; Romero González, Adrián; Cabrera Hernández, Daniel (Revista Cubana de Hematología, Inmunología y Hemoterapia, 2024)
Introduction: Essential thrombocythemia and primary myelofibrosis share the presence of JAK2, CALR and MPL mutations. In total, they comprise slightly more than 90 % of patients with these diseases. Objectives: To determine the behavior of the most frequent mutations in MPL and CALR genes in Cuban patients. Methods: An ambispective, descriptive and longitudinal study was performed at the Institute of Hematology and Immunology of Cuba, between 2010 and 2020. All patients with suspected essential thrombocythemia and primary myelofibrosis with valid DNA samples were included. CALR and MPL mutations were identified by real-time PCR. Results: Of the 53 patients studied, 67.9% were diagnosed with essential thrombocythemia, and 22.6% with primary myelofibrosis. In 90.6% it was possible to detect any of the driver mutations: 67.9% were positive for the JAK2V617F mutation, 13.2% for mutations in the gene coding for calreticulin and in 9.4% mutations in the MPL gene were identified. Conclusions: The behavior of the driver mutations JAK2V617F, CALR and MPL in the sample of Cuban patients with essential thrombocythemia and primary myelofibrosis was in correspondence with what is described in the majority of the investigations.